Manajemen Pengorganisasian Dakwah : Strategi Lembaga Dakwah MWC NU Kaliwungu dalam Mengatasi Tantangan Globalisasi - Nur Aenatul Khoria (Journal of Islamic Management, 2021)
This study aims to determine the management of the da'wah organization at MWC NU Kaliwungu and the strategy of the NU da'wah institution in overcoming the challenges of globalization. This study uses a da'wah science approach that focuses on the management principles of the da'wah organization. The data collection was obtained through an interview and library process that utilized reference sources in the form of books, journals, and other articles, both printed and online. Data analysis followed the Miles and Huberman model. The results of this study indicate that: First, the management of da'wah organization at MWC NU Kaliwungu in developing its da'wah tasks applies organizational management based on the forms of division of tasks. Second, the da'wah strategy carried out by MWC NU Kaliwungu in the face of the global industrial market which has begun to penetrate the Kaliwungu area which is marked by the establishment of KIK (Kendal Industrial Area), is more focused on reinforcing the teachings of NU's and Aswaja's to the public. . Therefore, the scholars developed a da'wah strategy through mental and spiritual strengthening activities with 1 billion sholawat with the community in each branch, held Lailatul Ijtima' regularly with religious leaders in the Kaliwungu- Kendal area, and used the media for da'wah by establishing cooperation with Radio Citra Kendal to be transferred to the MWC NU Da'wah Building.